Longitudinal NT‐proBNP: Associations With Echocardiographic Changes and Outcomes in Heart Failure - Kanako Teramoto; Wan Ting Tay; Jasper Tromp; Wouter Ouwerkerk; Tiew‐Hwa Katherine Teng; Chanchal Chandramouli; Oi Wah Liew; Jenny Chong; Katrina K. Poppe; Mayanna Lund; Gerry Devlin; Richard W. Troughton; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The relationship of serial NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) measurements with changes in cardiac features and outcomes in heart failure (HF) remains incompletely understood. We determined whether common clinical covariates impact these relationships. Methods and Results In 2 nationwide observational populations with HF, the relationship of serial NT‐proBNP measurements with serial echocardiographic parameters and outcomes was analyzed, further stratified by HF with reduced versus preserved left ventricular ejection fraction, inpatient versus outpatient enrollment, age, obesity, chronic kidney disease, atrial fibrillation, and attainment of ≥50% guideline‐recommended doses of renin‐angiotensin system inhibitors and β‐blockers. Among 1911 patients (mean±SD age, 65.1±13.4 years; 26.6% women; 62% inpatient and 38% outpatient), NT‐proBNP declined overall, with more rapid declines among inpatients, those with obesity, those with atrial fibrillation, and those attaining ≥50% guideline‐recommended doses. Each doubling of NT‐proBNP was associated with increases in left ventricular volume (by 6.1 mL), E/e′ (transmitral to mitral annular early diastolic velocity ratio) (by 1.4 points), left atrial volume (by 3.6 mL), and reduced left ventricular ejection fraction (by −2.1%). The effect sizes of these associations were lower among patients with HF with preserved ejection fraction, atrial fibrillation, or advanced age (Pinteraction<0.001). A landmark analysis identified that an SD increase in NT‐proBNP over 6 months was associated with a 27% increase in the risk of the composite event of HF hospitalization or all‐cause death between 6 months and 2 years (adjusted hazard ratio, 1.27 [95% CI, 1.15–1.40]; P<0.001). Conclusions The relationships between NT‐proBNP and structural/functional remodeling differed by age, presence of atrial fibrillation, and HF phenotypes. The association of increased NT‐proBNP with increased risk of adverse outcomes was consistent in all subgroups.